1991
DOI: 10.1063/1.105461
|View full text |Cite
|
Sign up to set email alerts
|

Density of states distribution in diamond thin films

Abstract: Space-charge-limited hole currents in nominally undoped diamond thin films have been studied using thin, highly boron-doped (p+) diamond layers as injecting contacts. The results obtained from these p+-p-Si structures have been analyzed to determine, for the first time, the bulk distribution of localized states N(E) in polycrystalline diamond thin films. The values of N(E), covering an energy range of about 0.8–0.6 eV above the valence band, indicate that the density of states at 0.8 eV is about 1015 cm−3 eV−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Previous authors have assigned such phenomena in undoped CVD diamond to the band of shallow hole traps centered at an energy approximately 0.61 eV from the valance band. 2,3 In contrast, photocurrent measurements from coplanar detectors using 4 When illuminated with long pulses of UV light, coplanar diamond detectors also demonstrate significant photocurrent persistence. 5 In one study using 200 nm irradiation from a deuterium lamp, a clear dependence was observed between photocurrent decay times and the nature of the metaldiamond contact structure.…”
mentioning
confidence: 97%
“…Previous authors have assigned such phenomena in undoped CVD diamond to the band of shallow hole traps centered at an energy approximately 0.61 eV from the valance band. 2,3 In contrast, photocurrent measurements from coplanar detectors using 4 When illuminated with long pulses of UV light, coplanar diamond detectors also demonstrate significant photocurrent persistence. 5 In one study using 200 nm irradiation from a deuterium lamp, a clear dependence was observed between photocurrent decay times and the nature of the metaldiamond contact structure.…”
mentioning
confidence: 97%
“…This conclusion is in contradiction to data of Mort, Machonkin, and Okumura, who propose p-type properties of intrinsic CVD diamond based on doping experiments. 6 Given the likely variability in preparation conditions and the high defect densities, this contradiction cannot be resolved based on the presented data. Applying a forward voltage reduces the built-in potential of the illuminated contact.…”
Section: Cr/au-diamond Contact Propertiesmentioning
confidence: 72%
“…However, disordered regions are expected to occur at grain boundaries that could explain that results. In the high temperature region the process follows a Space Charge Limited Current [6]. The exponent of non-ohmic component is near 4 indicating a existence of a band-tail with a high density of states increasing exponentially toward the conduction band where the carriers are emitted from deeper states into this bandtail.…”
Section: Resultsmentioning
confidence: 96%